Handbook of e-business security - Tavares, João Manuel R. S.; Mishra, Brojo Kishore 1979-; Kumar, Raghvendra 1987-; Zaman, Noor 1972-; Khari, Manju (CRC Press, Taylor & Francis Group, 2020)
There are a lot of e-business security concerns. Knowing about e-business security issues will likely help overcome them. Keep in mind, companies that have control over their e-business are likely to prosper most. In other words, setting up and maintaining a secure e-business is essential and important to business growth. This book covers state-of-the art practices in e-business security, including privacy, trust, security of transactions, big data, cloud computing, social network, and distributed systems
Literaturangaben
Keywords: Computersicherheit; Electronic Commerce; Business enterprises / Computer networks / Security measures; Computer security; Aufsatzsammlung